Note—A Note on the Single-Machine Multi-Product Lot Scheduling Problem - Haessler, Robert W.; Hogue, Steven L. (Management Science, 1976)
This note develops a procedure for automatically generating feasible solutions for the single-machine multi-product lot scheduling problem.